A kind of AlTiN-based hard coating and its preparation method and application

By controlling the proportion and crystal plane orientation of Al and Ti elements, combined with alloying doping of B and C, the AlTiN coating structure is optimized, and the problem of mechanical properties of AlTiN coating at high temperatures is solved, achieving high hardness, toughness and The controllability of wear resistance is suitable for different application fields.

CN115786849BActive Publication Date: 2024-12-24ZHUZHOU HUARUI PRECISION CUTTINGS TOOLS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211601130.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2024-12-24
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

The mechanical properties of AlTiN hard coatings decrease at high temperatures, and existing modification methods may introduce material defects, affecting performance.

Method used

By controlling the proportion and crystal plane orientation of Al and Ti elements, combining light element alloying doping of B and C, the formation of hexagonal phases is suppressed, the coating structure is optimized, and the appropriate crystal plane is selected for optimal growth.

Benefits of technology

The mechanical properties of the coating are controlled, the nanohardness, toughness and wear resistance are improved, the applicability is enhanced, and the tool service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115786849B_ABST
    Figure CN115786849B_ABST
Patent Text Reader

Abstract

The invention discloses an AlTiN-based hard coating and a preparation method and application thereof, and relates to the technical field of wear-resistant coatings; the hard coating is (AlTiN-based m Ti n ) x B y C 1‑(m+n)x‑y N; wherein, 1≤m / n≤3 and m+n=1, 0<n<1, 0<m<1; x≥0; y≥0; 1‑(m+n)x‑y≥0. The AlTiN-based hard coating of the present invention can maintain the excellent comprehensive performance of the AlTiN-based coating, while controlling the preferred orientation of the crystal structure of the coating material phase, achieving high hardness, toughness and wear resistance, and the coating performance has a tendency to be controllably adjusted. The preparation method is simple in process, has high process stability, is easy to operate in production, and can achieve large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wear-resistant coatings, and in particular is an AlTiN-based hard coating and a preparation method and application thereof. Background Art

[0002] The emergence of hard coatings is a technological innovation in industrial development. By depositing a wear-resistant, tough and high-temperature resistant coating on the surface of cutting tools, industrial molds and other types of substrates, industrial production efficiency and product life can be significantly improved, and costs can be greatly saved. AlTiN coatings are widely used due to their balanced performance in all aspects and strong versatility. However, as people become more and more aware of the advantages of coating protection, the application areas of coatings are increasing. The various components in each field are used differently and have different performance requirements. As a surface directly coated on the substrate, coatings also have higher requirements.

[0003] AlTiN hard coating is developed by introducing Al element on the basis of TiN coating. Al element partially replaces the lattice position of Ti element in face-centered cubic lattice (B1-NaCl type). The addition of Al element improves the high temperature performance of coating (red hardness and high temperature oxidation resistance). The excellent high temperature performance makes TiAlN coating widely used in high-speed cutting processing. Since AlTiN is essentially a supersaturated metastable structure, when the temperature is higher than 900℃, the coating further decomposes from the face-centered cubic solid solution phase c-Al(Ti)N structure to form a stable structure of h-AlN and c-TiN dual-phase structure, and the mechanical properties decrease rapidly. h-AlN belongs to the close-packed hexagonal phase structure (B4-wurtzite type), and its mechanical properties are poor and belong to the defective phase structure. Therefore, inhibiting the appearance and development of the wurtzite structure h-AlN phase of the deposited coating material is a very meaningful work for both high-speed cutting of tools and low-temperature wear conditions.

[0004] In the related art, the AlTiN coating system has been modified by adding various characteristic elements. In the related art, the solid solution of elements with larger atomic radius (such as Hf, Ta, W, Nb, Mo, Ru, etc.) doped in the AlTiN solid solution will cause lattice distortion effect, so that the film-based interface forms more complex non-coherent interfaces, which may cause defects inside the material and degrade the performance modification. In contrast, the introduction of characteristic elements with smaller atomic radius can be further modified while maintaining the original performance of the AlTiN-based coating. However, the composite structure of AlTiN nanocrystals wrapped by amorphous Si3N4 phase formed by adding Si element to the AlTiN coating, but the addition of Si reduces the solid solubility of Al in cubic phase TiN, which is easy to trigger the generation of hexagonal phase crystal structure, and the hardness softens sharply.

[0005] Therefore, it is necessary to provide an AlTiN-based hard coating whose crystal planes are preferentially oriented, so as to achieve a controlled adjustment of the coating properties and optimize the application of the coating. Summary of the invention

[0006] An object of the present invention is to provide an AlTiN-based hard coating to solve at least one aspect of the problems and defects raised in the above-mentioned background technology.

[0007] The present invention also provides a method for preparing the AlTiN-based hard coating.

[0008] The invention also provides application of the AlTiN-based hard coating.

[0009] Specifically, the first aspect of the present invention provides an AlTiN-based hard coating, wherein the hard coating is (Al m Ti n ) x B y C 1-(m+n)x-y N;

[0010] Among them, 1≤m / n≤3 and m+n=1, 0<n<1, 0<m<1; x≥0; y≥0; 1-(m+n)xy≥0;

[0011] The crystal plane orientation of the coating includes at least one of Fcc-Al(Ti)N(111), Fcc-Al(Ti)N(200) and Fcc-Al(Ti)N(220).

[0012] According to one technical solution of the coating technical solution of the present invention, at least the following beneficial effects are achieved:

[0013] In the present invention, the ratio of Al element and Ti element in the coating material is controlled, thereby achieving control over the mechanical properties of the coating; at the same time, the present invention also selects the crystal plane orientation of the coating, thereby achieving regulation of the nanohardness, toughness and wear resistance of the coating, thereby achieving the applicability of the coating.

[0014] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, m / n is between 1.5 and 2.

[0015] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-yIn N, 0.8≤x≤1.

[0016] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0.9≤x≤1.

[0017] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0.95≤x≤1.

[0018] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0.32≤x≤0.45.

[0019] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0≤y≤0.2.

[0020] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0≤y≤0.1.

[0021] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0≤y≤0.05.

[0022] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0.025≤y≤0.05.

[0023] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-yIn N, 0≤1-(m+n)xy≤0.2.

[0024] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0≤1-(m+n)xy≤0.1.

[0025] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0≤1-(m+n)xy≤0.05.

[0026] According to some embodiments of the present invention, the (Al m Ti n ) x B y C 1-(m+n)x-y In N, 0.025≤1-(m+n)xy≤0.05.

[0027] According to some embodiments of the present invention, the coating has a thickness of 0.5 μm to 10 μm.

[0028] According to some embodiments of the present invention, the coating has a thickness of 0.5 μm to 5 μm.

[0029] According to some embodiments of the present invention, the coating has a thickness of 2 μm to 5 μm.

[0030] According to some embodiments of the present invention, the coating has a thickness of 2 μm to 3 μm.

[0031] According to some embodiments of the present invention, the nanohardness of the coating is above 32 GPa.

[0032] According to some embodiments of the present invention, the nanohardness of the coating is 32 GPa~40 GPa.

[0033] According to some embodiments of the present invention, the H of the coating 3 / E 2 Above 0.23.

[0034] According to some embodiments of the present invention, the H of the coating 3 / E 2 Between 0.23 and 0.4.

[0035] According to some embodiments of the present invention, the H of the coating 3 / E2 Between 0.25 and 0.4.

[0036] According to some embodiments of the present invention, the H of the coating 3 / E 2 Between 0.25 and 0.35.

[0037] According to some embodiments of the present invention, the coating layer is one of an AlTiN layer, an AlTiCN layer, an AlTiBN layer and an AlTiBCN layer.

[0038] According to some embodiments of the present invention, the AlTiN layer is Al 0.6~0.65 Ti 0.35~0.4 N layers.

[0039] According to some embodiments of the present invention, the AlTiCN layer is Al 0.6~0.65 Ti 0.35~0.4 C 0.025~0.05 N layers.

[0040] According to some embodiments of the present invention, the AlTiBN layer is Al 0.6~0.65 Ti 0.35~0.4 B 0.025~0.05 N layers.

[0041] According to some embodiments of the present invention, the AlTiBCN layer is Al 0.6~0.63 Ti 0.35~0.38 C 0.025~ 0.05 B 0.025~0.05 N layers.

[0042] In the present invention, the light elements B and C are selected to maintain the original AlTiN material phase structure and further adjust the preferential growth of the crystal plane to modify the coating.

[0043] A second aspect of the present invention provides a method for preparing the above-mentioned AlTiN-based hard coating, comprising the following steps:

[0044] After activating the substrate, the AlTiN-based hard coating is prepared by vapor deposition;

[0045] The current of the vapor deposition is 100A-250A.

[0046] According to one technical solution of the preparation method technical solution of the present invention, at least the following beneficial effects are achieved:

[0047] The invention controls the preparation method, thereby inhibiting the generation of a soft phase in the coating and reducing defects in the coating.

[0048] According to some embodiments of the present invention, the activation is ion etching;

[0049] The ion etching time is 30min~60min;

[0050] The ion source voltage in the ion etching is 120V~250V.

[0051] According to some embodiments of the present invention, the vapor deposition is cathodic arc ion plating.

[0052] According to some embodiments of the present invention, the bias voltage of the cathodic arc ion plating is 40V~150V.

[0053] According to some embodiments of the present invention, the vacuum degree of the cathodic arc ion plating is 1Pa~10Pa.

[0054] According to some embodiments of the present invention, the rotation speed of the workpiece holder during the cathode arc ion plating process is 1.58 r / min~2.63 r / min.

[0055] According to some embodiments of the present invention, the atmosphere of the cathodic arc ion plating is nitrogen.

[0056] According to some embodiments of the present invention, the cathodic arc ion plating time is 20 min to 200 min.

[0057] According to some embodiments of the present invention, the substrate is sequentially heated, hydrogen ion thermally reduced and activated.

[0058] According to some embodiments of the present invention, the final temperature of the heating is 500°C to 600°C.

[0059] According to some embodiments of the present invention, the atmosphere for the hydrogen ion thermal reduction is a mixed gas of argon and hydrogen.

[0060] According to some embodiments of the present invention, the vacuum degree of the hydrogen ion thermal reduction is 0.1Pa~1.0Pa.

[0061] According to some embodiments of the present invention, the voltage of the hydrogen ion thermal reduction is 30V~80V.

[0062] According to some embodiments of the present invention, the ion source current during the hydrogen ion thermal reduction process is 100A~220A.

[0063] According to some embodiments of the present invention, the time of the hydrogen ion thermal reduction is 15 min to 35 min.

[0064] According to some embodiments of the present invention, the current of the ion etching is 150A~250A.

[0065] According to some embodiments of the present invention, the vacuum degree of the ion etching is 0.1Pa~10Pa.

[0066] According to some embodiments of the present invention, the method for preparing the substrate comprises the following steps:

[0067] The powder metallurgy method is used for wet grinding, spray drying, pressing, sintering and subsequent mechanical processing and process treatment.

[0068] According to some embodiments of the present invention, the substrate is subjected to sandblasting, polishing, cleaning, radiation heating, hydrogen ion heating and etching activation treatments.

[0069] According to some embodiments of the present invention, the target material for vapor deposition is an AlTi-based target material.

[0070] According to some embodiments of the present invention, the AlTi-based target is one of an AlTi target, an AlTiC target, an AlTiB target and an AlTiBC target.

[0071] According to some embodiments of the present invention, after the vapor deposition is completed, the product is naturally cooled under vacuum to a temperature less than 200°C.

[0072] The third aspect of the present invention provides the use of the above-mentioned AlTiN-based hard coating in the preparation of cutting tools or industrial molds.

[0073] According to some embodiments of the present invention, the cutting tool is a turning insert.

[0074] According to some embodiments of the present invention, the cutting tool is a cemented carbide tool. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0076] Figure 1 The XRD phase spectra of the coatings prepared in Examples 1-2 of the present invention and the comparative example are shown.

[0077] Figure 2 The XRD phase spectra of the coatings prepared in Examples 3 to 5 of the present invention and the comparative example are shown.

[0078] Figure 3 This is a photo of the coating indentation morphology of the comparative example of the present invention.

[0079] Figure 4 This is a photo of the coating indentation morphology of Example 1 of the present invention.

[0080] Figure 5 This is a photo of the coating indentation morphology of Example 2 of the present invention.

[0081] Figure 6 This is a photo of the coating indentation morphology of Example 3 of the present invention.

[0082] Figure 7 This is a photo of the coating indentation morphology of Example 4 of the present invention.

[0083] Figure 8 This is a photo of the coating indentation morphology of Example 5 of the present invention. DETAILED DESCRIPTION

[0084] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0085] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0086] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0087] In the selected embodiment of the present invention, the substrate is selected from alloy strips or CNC tools.

[0088] The alloy strips or CNC tools are all made by powder metallurgy method, and the cemented carbide matrix is ​​composed of WC hard phase, Co bonding phase and composite additives.

[0089] The size of the alloy bar (the material of the alloy bar is specifically selected to be M30 base grade) is 20 mm (length) × 8 mm (width) × 6 mm (height).

[0090] The CNC tool is a WNMG080408-BM carbide turning insert. Example 1

[0091] This embodiment is an AlTiNi based hard coating. m Ti n )x B y C 1-(m+n)x-y N.

[0092] In this embodiment, m / n=1.7, m+n=1, x=1, y=0, 1-(m+n)xy=0.

[0093] In this embodiment, the coating is (Al 17 / 27 Ti 10 / 27 )1B0C0N Al 17 / 27 Ti 10 / 27 N (the atomic composition is the theoretical design value, convert the fraction into a decimal to approximate: Al 0.63 Ti 0.37 N).

[0094] The thickness of the coating in this embodiment is 2.91 μm.

[0095] The method for preparing the coating in this embodiment comprises the following steps:

[0096] S1, place the substrate in a vacuum of 5×10 -2 After heating to 550°C under the condition of Pa, thermal reduction is performed using a reducing gas to obtain a thermally reduced substrate;

[0097] The reducing gas is a mixture of argon and hydrogen (the volume fraction of hydrogen is 5%).

[0098] The vacuum degree of thermal reduction is 1.0 Pa, and the time of thermal reduction is 30 min;

[0099] The bias voltage of thermal reduction is 80 V, the ion source current is 200 A, and the thermal reduction is plasma thermal reduction.

[0100] S2, ion etching and activating the thermally reduced substrate using argon gas to obtain an activated substrate;

[0101] The process parameters of ion etching are as follows:

[0102] The atmosphere was argon, the vacuum degree was 1.0 Pa, the voltage was 200 V, the ion source current was 200 A, and the etching activation time was 30 min.

[0103] S3, preparing a coating on the surface of the activated substrate by cathode arc ion plating;

[0104] The process parameters of cathodic arc ion plating are as follows:

[0105] The target material is Al 0.63 Ti 0.37N alloy target (purity is 99.99%), the atmosphere is nitrogen, the workpiece holder speed is 2.11r / min, the vacuum degree is 0.5Pa, the current is 250A, the voltage is 60V, and the deposition time is 100min.

[0106] S4. After the coating is prepared, turn off all arc sources, bias power supply, heating power supply, and gas, and cool naturally under vacuum until the product temperature is less than 200°C.

[0107] In this embodiment, the coating is deposited on the alloy strip and the CNC tool respectively; and two groups of performance test products are obtained. Example 2

[0108] This embodiment is an AlTiNi based hard coating. m Ti n ) x B y C 1-(m+n)x-y N.

[0109] In this embodiment, m / n=1.5, m+n=1, x=1, y=0, and 1-(m+n)xy=0.

[0110] In this embodiment, the coating is (Al 0.6 Ti 0.4 )1B0C0N Al 0.6 Ti 0.4 N (atomic composition is theoretical design value).

[0111] The thickness of the coating in this embodiment is 2.75 μm.

[0112] The preparation method of the coating in this embodiment is carried out in accordance with Example 1, that is, the target material (Al 60 Ti 40 Alloy target, purity is 99.99%), but the process parameters remain unchanged. Example 3

[0113] This embodiment is an AlTiNi based hard coating. m Ti n ) x B y C 1-(m+n)x-y N.

[0114] In this embodiment, m / n=2, m+n=1, x=0.95, y=0.05, 1-(m+n)xy=0.

[0115] In this embodiment, the coating is (Al 2 / 3 Ti 1 / 3 ) 0.95 B0.05 Al in C0N 19 / 30 Ti 19 / 60 B 0.05 N (atomic composition is the theoretical design value, convert the fraction into a decimal to get the approximate value: Al 0.634 Ti 0.316 B 0.05 N).

[0116] The thickness of the coating in this embodiment is 2.67 μm.

[0117] The preparation method of the coating in this embodiment is carried out in accordance with Example 1, that is, the target material (Al 0.634 Ti 0.316 B 0.05 Alloy target, purity is 99.99%), but the process parameters remain unchanged. Example 4

[0118] This embodiment is an AlTiNi based hard coating. m Ti n ) x B y C 1-(m+n)x-y N.

[0119] In this embodiment, m / n=2, m+n=1, x=0.975, y=0.025, 1-(m+n)xy=0.

[0120] In this embodiment, the coating is (Al 2 / 3 Ti 1 / 3 ) 0.975 B 0.025 Al in C0N 0.65 Ti 0.325 B 0.025 N (atomic composition is theoretical design value).

[0121] The thickness of the coating in this embodiment is 2.71 μm.

[0122] The preparation method of the coating in this embodiment is carried out in accordance with Example 1, that is, the target material (Al 0.65 Ti 0.325 B 0.025 Alloy target, purity is 99.99%), but the process parameters remain unchanged. Example 5

[0123] This embodiment is an AlTiNi based hard coating. m Ti n ) x B y C 1-(m+n)x-y N.

[0124] In this embodiment, m / n=2, m+n=1, x=0.975, y=0, 1-(m+n)xy=0.025.

[0125] In this embodiment, the coating is (Al 2 / 3 Ti 1 / 3 ) 0.975 B0C 0.025 N Al 0.65 Ti 0.325 C 0.025 N (atomic composition is theoretical design value).

[0126] The thickness of the coating in this embodiment is 2.94 μm.

[0127] The preparation method of the coating in this embodiment is carried out in accordance with Example 1, that is, the target material (Al 0.65 Ti 0.325 C 0.025 Alloy target, purity is 99.99%), but the process parameters remain unchanged. Comparative Example

[0128] This comparative example is an AlTiNi based hard coating. m Ti n ) x B y C 1-(m+n)x-y N.

[0129] In this comparative example, m / n=2, m+n=1, x=1, y=0, and 1-(m+n)xy=0.

[0130] In this comparative example, the coating is (Al 2 / 3 Ti 1 / 3 )1B0C0N Al 2 / 3 Ti 1 / 3 N (the atomic composition is the theoretical design value, convert the fraction into a decimal to approximate: Al 0.667 Ti 0.333 N).

[0131] The thickness of the coating in this comparative example is 2.8 μm.

[0132] The preparation method of the coating in this comparative example is carried out in accordance with Example 1, that is, the target material (Al 0.667 Ti 0.333 N alloy target, purity is 99.99%), but the process parameters remain unchanged.

[0133] like Figure 1As shown, an X-ray diffractometer (Bruker, D8 / Advance) was used to perform XRD scanning on the surface of the alloy strip samples of the coatings of the above-mentioned Examples 1-2 and the comparative example. The measured spectrum data was analyzed for physical phases using MDI jade6 software. The results showed that for the AlTiN coating without B and C alloying doping, as the ratio of Al and Ti components was adjusted, the m / n value decreased from 2 to 1.5 (i.e., the Al component was reduced). Comparative Example Al 2 / 3 Ti 1 / 3 The XRD diffraction peaks of the N coating are face-centered cubic solid solution phase c-Al(Ti)N and Hexagonal close-packed phase w-Al(Ti)N has a strong orientation on the (10-10) crystal plane. Compared with the XRD diffraction peaks of the comparative coating, as the Al element component of the coatings of Example 1 and Example 2 decreases, the hexagonal w-Al(Ti)N is suppressed, and the c-Al(Ti)N structure texture orientation on the (200) and (111) crystal planes is enhanced. However, the mechanical properties of the w-AlN crystal structure are poor, which will reduce the service life and stability of the tool. The cubic solid solution structure c-Al(Ti)N of (200) and (111) has good hardness and toughness. Therefore, it is proved that by adjusting the ratio of Al and Ti elements, the physical phase is optimized, thereby improving the performance of the tool.

[0134] like Figure 2 As shown, an X-ray diffractometer (Bruker, D8 / Advance) was also used to scan the surface of the alloy strip samples of the above-mentioned embodiments 3 to 5 and the comparative example coating. The measured spectrum data was analyzed for the phase using MDI jade6 software. The results showed that: for the AlTiBCN coating doped with B and C alloying, the ratio of Al and Ti components was fixed at m:n=2, and the doping amount of B and C elements was adjusted accordingly. 2 / 3 Ti 1 / 3 The XRD diffraction peaks of the N coating are face-centered cubic solid solution phase c-Al(Ti)N of the (111), (200) and (220) crystal planes. Compared with the XRD diffraction peaks of the c-Al(Ti)N structure of the comparative coating, Example 3 has a (111) crystal plane peak with a strong preferred orientation, Example 4 has a (200) crystal plane peak with a strong preferred orientation, and Example 5 has a (220) crystal plane peak with a strong preferred orientation. Due to c -Al(Ti)N Different crystal planes (111), (200) and (220)], resulting in different performance changes in the coating properties, such as high hardness, toughness and strong wear resistance. alloy Doping amount , the controllability of the preferred orientation of the crystal plane is manifested in the physical phase, thus realizing the controllable adjustment of the performance tendency of the tool.

[0135] Adopting Anton Paar's NHT 3 The nanoindentation module measures the nanohardness and elastic modulus of the polished strip samples of the coating alloy of the embodiment and the comparative example. In order to ensure the accuracy of the measurement results, the surface of the sample to be tested is wet-sandblasted to reduce the influence of droplets on the coating surface. At the same time, 30 points of each sample are measured and the average value is taken. The test results are shown in Table 1.

[0136] Table 1 Nanoindentation test results of tool coatings of Examples 1 to 5 and Comparative Examples

[0137]

[0138] H 3 / E 2 The value represents the ability of the coating material to resist plastic deformation, and the larger the value, the better the toughness. The results show that compared with the comparative example, as the Al element component is lowered, the hardness and toughness of Examples 1 and 2 gradually increase, which also shows that optimizing the phase orientation is helpful to improve the coating performance.

[0139] Compared with the comparative example, Examples 3 to 5 have a significant improvement, and Example 3 has the highest hardness, Example 4 has the best toughness, and Example 5 has a balanced increase in both hardness and toughness. This shows that the controllability of the preferred orientation of different crystal planes makes the performance of the material change with different tendencies.

[0140] Figures 3 to 8 The coating bonding strength was evaluated by the indentation method using a diamond indenter for Examples 1 to 5 of the present invention and the comparative example. The Rockwell hardness tester was used to press the coating to be tested at 60Kgf, 100Kgf and 150Kgf, respectively. Then, the overall and local peeling of the coating cracks around the indentation was observed by scanning electron microscopy, and the toughness and adhesion strength of the coating were evaluated. The coating indentation morphology photos show that the adhesion levels of the comparative example and Examples 1 to 5 are: HF5 (comparative example), HF5 (Example 1), HF4 (Example 2), HF2 (Example 3), HF1 (Example 4), HF3 (Example 5). It shows that the performance of the coating can be well improved by adjusting the proportion of the components and coordinating with alloying doping, so that the coating performance can achieve the purpose of tendency regulation.

[0141] The products obtained by using a CNC tool (WNMG080408-BM hard alloy stainless steel turning tool) as the substrate in the comparative example and embodiments 1 to 5 were tested using the following parameters:

[0142] Feed per tooth f x The machining method is continuous turning of the outer circle, and the axial cutting depth is a p 1mm, processed material 1Cr18Ni9Ti, linear speed Ve The cutting speed is 240m / min. This cutting parameter belongs to high speed and small feed, and is mainly used to evaluate the hardness and wear resistance of the coating. The test results are shown in Table 2.

[0143] Table 2 Cutting performance test results of Examples 1 to 5 of the present invention and the comparative example under high speed and low feed conditions

[0144]

[0145] The same life and full life comprehensive judgment are adopted. When the same time is 10min and the same life, the wear failure of the back tool face is as follows: Example 3> Example 4> Example 5> Example 1> Example 2≈ Comparative Example. The length of the full life cutting time: Example 3> Example 4> Example 5> Example 1> Comparative Example> Example 2. It can be almost confirmed by the hardness index of the mechanical properties measured by the above-mentioned nanoindentation. At the same time, it also shows that by regulating the preferential orientation of different crystal planes of the coating and suppressing defect phases, the hardness of the coating can be tended to be enhanced, which has great advantages in the application under the wear-resistant working conditions of high speed and low feed.

[0146] The products obtained by using a CNC tool (WNMG080408-BM hard alloy stainless steel turning tool) as the substrate in the comparative example and embodiments 1 to 5 were tested using the following parameters:

[0147] Feed per tooth f x The machining method is external continuous turning, and the axial cutting depth is a p 1mm, processed material 1Cr18Ni9Ti, linear speed V e The cutting speed is 150m / min. This cutting parameter belongs to low speed and high feed, and is mainly used to evaluate the hardness and wear resistance of the coating. The test results are shown in Table 3.

[0148] Table 3 Cutting performance test results of Examples 1 to 5 of the present invention and the comparative example under low speed and high feed conditions

[0149]

[0150] A cemented carbide stainless steel turning tool with the CNC tool model of WNMG080408-BM was selected to deposit the coatings of the comparison example and Examples 1-5. The cutting performance was compared according to the cutting conditions and specific parameters shown in Table 3. This cutting parameter belongs to low speed and large feed, and is mainly intended to evaluate the coating's ability to resist plastic deformation. The same life and full life comprehensive judgment was adopted. When the same time and life were 15 minutes, the wear failure of the back tool face was as follows: Example 4> Example 5> Example 3> Example 2> Example 1≈Comparative Example. The length of the full life cutting time: Example 4> Example 5> Example 3> Example 2> Example 1> Comparative Example. It is almost the same as the mechanical properties measured by the nanoindentation H mentioned above. 3 / E 2 It also shows that by regulating the preferred orientation of different crystal planes of the coating and suppressing defect phases, the coating's ability to resist plastic deformation can be enhanced, which has great advantages in low-speed impact conditions such as low-speed and high-feed.

[0151] The products obtained by using a CNC tool (WNMG080408-BM hard alloy stainless steel turning tool) as the substrate in the comparative example and embodiments 1 to 5 were tested using the following parameters:

[0152] Feed per tooth f x The machining method is external continuous turning, and the axial cutting depth is a p 2mm, processed material 1Cr18Ni9Ti, linear speed V e The cutting speed is 170m / min. This cutting parameter belongs to medium speed, high feed and large cutting depth, and is mainly used to evaluate the hardness and wear resistance of the coating. The test results are shown in Table 4.

[0153] Table 4 Cutting performance test results of Examples 1 to 5 of the present invention and the comparative example at medium speed, high feed and large cutting depth

[0154]

[0155] A cemented carbide stainless steel turning tool with a CNC tool model of WNMG080408-BM was selected to deposit the coatings of the comparative example and Examples 1 to 5. The cutting performance was compared according to the cutting conditions and specific parameters shown in Table 4. This cutting parameter belongs to medium speed, large feed and large cutting depth, and mainly tends to evaluate the comprehensive performance of the hardness and plastic deformation resistance of the coating. The same life and full life comprehensive judgment was adopted. When the same time was 10min and the same life, the wear failure of the back tool face was as follows: Example 4> Example 5> Example 1> Comparative Example> Example 2≈ Example 3. The length of the full life cutting time: Example 4> Example 5> Example 1> Comparative Example> Example 2≈ Example 3. It can be found that the mechanical properties and adhesion grade performance measured by the above-mentioned nanoindentation are balanced. It also shows that by regulating the preferred orientation of different crystal planes of the coating and suppressing defect phases, the comprehensive performance of the coating can be tended to be enhanced, and it has great advantages in application under high temperature and strong impact conditions such as medium speed, large feed and large cutting depth.

[0156] In summary, the present invention provides an AlTiN-based hard coating, and the coating performance and aluminum content have a certain linear relationship. A higher aluminum content will cause the cubic phase to become unstable. In the present invention, the hardness of the coating can be maintained by stabilizing the cubic AlTiN phase. The present invention achieves the suppression of the formation of the hexagonal soft phase in the coating by regulating the ratio of Al and Ti in the coating, optimizes the physical phase structure of the coating, and makes the coating material have fewer defects. At the same time, light elements with smaller atomic radius of B and C are selected for alloying and doping, so as to maintain the original physical phase structure of the AlTiN material and further control the preferential growth of the crystal plane to modify the coating. Due to the differences in the structural characteristics of different crystal planes [(111), (200) and (220)] of c-Al(Ti)N, specifically including: a. Different crystal plane spacing and unit cell density lead to hardness differences, and different slip degrees of different crystal planes in the face-centered cubic slip system have different dislocation strengthening effects, so that the coating has different strengths and toughness. Thus, the tendency of high hardness, toughness and strong wear resistance of the coating performance is controllably adjusted. The applicability of coating performance in different application fields is optimized to maximize the value of coating performance. The present invention controls the sputtering target source prepared by the powder metallurgy process, and its components are alloy targets of Al, Ti, C and B with a suitable stoichiometric ratio, and then cooperates with the preparation process to obtain a modified homogeneous AlTiN-based hard coating. The preparation method of the present invention has a simple process, high process stability, easy production operation, and can achieve large-scale production.

Claims

1. An AlTiN-based hard coating, characterized in that: The hard coating is (Al m Ti n ) x B y C 1-(m+n)x-y N; Among them, 1≤m / n≤3; m+n=1, 0<n<1, 0<m<1; x≥0; y≥0; 1-(m+n)xy≥0; The crystal plane orientation of the coating includes at least one of Fcc-Al(Ti)N(111), Fcc-Al(Ti)N(200) and Fcc-Al(Ti)N(220); The H of the hard coating 3 / E 2 Between 0.25 and 0.4; The AlTiN-based hard coating is prepared by cathode arc ion plating; The arc source current of the cathode arc ion plating is 250A; The bias voltage of the cathode arc ion plating is 40V~60V; The vacuum degree of the cathode arc ion plating is 0.5 Pa; The workpiece support rotation speed during the cathode arc ion plating process is 2.11r / min~2.63r / min; The atmosphere of the cathode arc ion plating is nitrogen; The cathode arc ion plating time is 20min to 100min.

2. The AlTiN-based hard coating according to claim 1, characterized in that: The m Ti n ) x B y C 1-(m+n)x-y In N, 0.8≤x≤1.

3. The AlTiN-based hard coating according to claim 1, characterized in that: The m Ti n ) x B y C 1-(m+n)x-y In N, 0≤y≤0.

2.

4. The AlTiN-based hard coating according to claim 1, characterized in that: The m Ti n ) x B y C 1-(m+n)x-y In N, 0≤1-(m+n)xy≤0.

2.

5. The AlTiN-based hard coating according to claim 1, characterized in that: The coating has a thickness of 0.5 μm to 10 μm.

6. The AlTiN-based hard coating according to claim 1, characterized in that: The coating layer is one of an AlTiN layer, an AlTiCN layer, an AlTiBN layer and an AlTiBCN layer.

7. A method for preparing an AlTiN-based hard coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: After subjecting the substrate to hydrogen ion thermal reduction and activation treatment, the AlTiN-based hard coating is obtained by cathode arc ion plating; The arc source current of the cathode arc ion plating is 250A; The bias voltage of the cathode arc ion plating is 40V~60V; The vacuum degree of the cathode arc ion plating is 0.5 Pa; The workpiece support rotation speed during the cathode arc ion plating process is 2.11r / min~2.63r / min; The atmosphere of the cathode arc ion plating is nitrogen; The cathode arc ion plating time is 20min to 100min.

8. The method according to claim 7, characterized in that The hydrogen ion thermal reduction time is 15 min to 35 min; the ion source current of the hydrogen ion reduction is 100 A to 220 A.

9. The method according to claim 7, characterized in that: The activation is ion etching; The ion etching time is 30min~60min; The ion source voltage in the ion etching is 120V~250V.

10. Use of the AlTiN-based hard coating according to any one of claims 1 to 6 in the preparation of cutting tools or industrial molds.